2011
DOI: 10.1038/ncomms1546
|View full text |Cite
|
Sign up to set email alerts
|

Functionalized arrays of Raman-enhancing nanoparticles for capture and culture-free analysis of bacteria in human blood

Abstract: Detecting bacteria in clinical samples without using time-consuming culture processes would allow rapid diagnoses. such a culture-free detection method requires the capture and analysis of bacteria from a body fluid, which are usually of complicated composition. Here we show that coating Ag-nanoparticle arrays with vancomycin (Van) can provide label-free analysis of bacteria via surface-enhanced Raman spectroscopy (sERs), leading to a ~1,000-fold increase in bacteria capture, without introducing significant sp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
126
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 244 publications
(129 citation statements)
references
References 44 publications
1
126
0
Order By: Relevance
“…37 Therefore, vancomycinmodified nanostructures can interact strongly with a broad range of Gram-positive and Gram-negative bacteria and thus can be used as affinity probes to selectively trap these organisms. 21,53 On the basis of the knowledge in the previous studies combined with our experimental results, the plausible mechanism of the enhanced antibacterial activity of Van/Fe 3 O 4 @ SiO 2 @Ag microflowers is proposed in Figure 7A. The Van/ Fe 3 O 4 @SiO 2 @Ag microflower can interact with the cell wall of the bacteria and adhere onto the bacterial surface …”
Section: @Ag Microflowersmentioning
confidence: 99%
“…37 Therefore, vancomycinmodified nanostructures can interact strongly with a broad range of Gram-positive and Gram-negative bacteria and thus can be used as affinity probes to selectively trap these organisms. 21,53 On the basis of the knowledge in the previous studies combined with our experimental results, the plausible mechanism of the enhanced antibacterial activity of Van/Fe 3 O 4 @ SiO 2 @Ag microflowers is proposed in Figure 7A. The Van/ Fe 3 O 4 @SiO 2 @Ag microflower can interact with the cell wall of the bacteria and adhere onto the bacterial surface …”
Section: @Ag Microflowersmentioning
confidence: 99%
“…In particular, surface‐enhanced Raman scattering spectroscopy is able to enhance the signal by 11 orders of magnitude, which is sufficient for single‐molecule detection 14. Therefore, micro‐Raman spectroscopy has been utilized to monitor bacterial development, probe cellular stress response, analyze functions of microbial communities, and detect clinically relevant bacteria in laboratory settings 11, 12, 15, 16, 17, 18, 19, 20, 21, 22, 23, 24. We also utilized Raman microspectroscopy to probe bacterial metabolism and interactions9, 25 and isolate single cells 26.…”
Section: Introductionmentioning
confidence: 99%
“…Such a study is difficult but immensely useful because the hybrid (metal-semiconductor) nanostructures can be used for a wide range of applications such as SERS, [16][17][18] photonics, 4,5 renewable energy 3 and biomedicine. [19][20][21] This study addresses whether the newly observed optical effects, LMR and SWs in an NW system, can positively affect the plasmonic E field for photonic applications.…”
Section: Introductionmentioning
confidence: 99%